Comparing of the Course of Pharmaceutically Resistant Epilepsy Forms in Patients Treated with Ketogenic Diet and Tissue Transplantation - Tantsura, L. M.; Shatillo, A. V. (Problems of Cryobiology and Cryomedicine, 2006)
Results of treatment by nonmedicamental methods: ketogenic diet (KD) and tissue transplantation (TT) of cryopreserved embryonic neuronal tissue in patients with pharmacoresistent epilepsy were presented in the article. Comparative analysis of effectiveness and peculiarities of their applications in clinic of pharmacoresistent epilepsy was carried-out. On the base of investigation results a conclusion about KD and TT usefulness, with taking in account their treatment effect, indications and contraindications was made.